The Influence of Injectable Platelet Rich Fibrin on Osteogenesis as a Material for Periodontal Regenerative Treatment - Marapandi Cakra; Kwartarini Murdiastuti; Sri Pramestry Lastianny (Interdental Jurnal Kedokteran Gigi (IJKG), 2024)
Introduction: Periodontal regenerative treatment involves various aspects of achieving healing of soft and hard tissues, thus requiring materials with good regenerative stimulation capabilities. Injectable - Platelet Rich Fibrin or I-PRF is one of the most commonly used materials in regenerative periodontal and has a high success rate in bone regeneration as well as soft tissue in periodontal surgeries. The aim of this review is to provide an overview of the influence of I-PRF on osteogenesis as a material for periodontal regenerative treatment. Literature Review: I-PRF has a good ability in achieving regeneration of both soft and hard periodontal tissue. The advantages of I-PRF over conventional PRF are higher levels of leukocytes and easier application. Conclusion: I-PRF is ideal for achieving osteogenesis and periodontal tissue regeneration in regenerative periodontal care.